(untitled) (Applied Biological Research, 2023)
The BET BRD4 proteins, involved in cancer, are of prime importance in developing anticancer drugs. Cancer is marked by the uncontrolled growtof abnormal cells anywhere in the body with the potential to spread or invade other body parts. The core nature of disease lies in defying normal cell signals, be it anti-growth signals, death signals or apoptosis, and tissue invasion metastasis. In present work, we have designed and tested novel quinazolinone-based derivatives to establish them as a better anticancer agent against the BRD4 target. The selection of BRD4 protein in this work is based on earlier findings that reported the role of BRD4 in various cancers such as lymphoma, multiple myeloma, acute myeloid leukemia, acute lymphoblastic leukemia, chronic myeloid leukemia, solid tumours, prostate cancer, nervous system tumour, colorectal cancer, and breast cancer. Molecular docking was performed by using Glide docking module of the Schrodinger suite. The XP Glide docking studies, ADME (absorption, distribution, metabolism, excretion) profile test, binding energy calculations, and drug-likeness was performed to get the best BRD4 inhibitor ligand. Out of 16 quinazolinone derivates, ten ligands had better XP Glide score, 4 were marginally less, and 2 gave poor score than the standard drug LY2 (-6.779 kcal mol-1). The best ligand had a score of -9.866 kcal mol-1 which was 45% more efficient than LY2, so appears to be more effective and potent anticancer inhibitor ligands for BRD4 protein.